2008
DOI: 10.4025/actasciagron.v30i3.3555
|View full text |Cite
|
Sign up to set email alerts
|

Resposta da aveia preta (<em>Avena strigosa</em> schreb) à irrigação por aspersão e adubação nitrogenada

Abstract: RESUMO. O objetivo do estudo foi avaliar os efeitos da adubação nitrogenada e da irrigação por aspersão no crescimento e na produção de massa seca (MS) da aveia preta (Avena strigosa Schreb). Foram avaliadas quatro doses de nitrogênio (0, 50, 100 e 150 kg de N ha-1) e, também, a presença ou ausência de irrigação. Foram determinadas as seguintes variáveis: altura de planta, produção de massa seca, taxa de crescimento e o teor de MS. Quando irrigada, a altura da planta foi maior, refletindo maior produção de mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…Luz et al [27] 0, 50, 100, and 150 kg N ha −1 , respectively, lower than those found in the present work. Results of sorghum and black oat MV show high response to N fertilization, but it is also important to consider the genotypes selection, region climate, and especially rainfall distribution.…”
Section: Discussioncontrasting
confidence: 56%
“…Luz et al [27] 0, 50, 100, and 150 kg N ha −1 , respectively, lower than those found in the present work. Results of sorghum and black oat MV show high response to N fertilization, but it is also important to consider the genotypes selection, region climate, and especially rainfall distribution.…”
Section: Discussioncontrasting
confidence: 56%
“…Highest oats biomass yield were reported by Primavesi et al (2002) and Luz et al (2008), the latter authors emphasizing the superiority of irrigation to promote increased biomass production.…”
Section: Oats Biomassmentioning
confidence: 94%